2021
DOI: 10.3390/cells10071782
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Metabostemness and Metabolic Reprogramming via P2X7 Receptor

Abstract: The heterogeneity of tumor cell mass and the plasticity of cancer cell phenotypes in solid tumors allow for the insurgence of resistant and metastatic cells, responsible for cancer patients’ clinical management’s main challenges. Among several factors that are responsible for increased cancer aggression, metabolic reprogramming is recently emerging as an ultimate cancer hallmark, as it is central for cancer cell survival and self-renewal, metastasis and chemoresistance. The P2X7 receptor, whose expression is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 114 publications
(172 reference statements)
0
13
0
Order By: Relevance
“…P2RX7 receptor is known to play a role in energy metabolism and has been shown to aid in cellular adaptations to adverse growth conditions including serum starvation and low glucose via metabolic reprogramming [59,60]. Furthermore, this P2RX7 mediated metabolic reprogramming has also been associated with increased cancer stemness, chemoresistance and ultimately metastasis [61,62]. It is therefore likely that P2RX7 confers a pro-survival adaptation under nutrient deprived hypoxic conditions that exist within the tumour mass, and inhibition of the receptor leads to increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…P2RX7 receptor is known to play a role in energy metabolism and has been shown to aid in cellular adaptations to adverse growth conditions including serum starvation and low glucose via metabolic reprogramming [59,60]. Furthermore, this P2RX7 mediated metabolic reprogramming has also been associated with increased cancer stemness, chemoresistance and ultimately metastasis [61,62]. It is therefore likely that P2RX7 confers a pro-survival adaptation under nutrient deprived hypoxic conditions that exist within the tumour mass, and inhibition of the receptor leads to increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This potentially serves as a positive feedback loop in cancer proliferation in which there is a continuous loop of increased extracellular ATP concentration leading to increase purinergic receptor activation followed by PI3K/Akt pathway activation. The activation of PI3K/Akt also suggests that P2X 7 R may help maintain stem cell-like populations in tumors ( Rabelo et al, 2021 ). It has also been shown in human embryonic kidney cells that P2X 7 R-expressing tumors were characterized by an increased expression of the transcription factor NFATc1 which conferred increased proliferative capability ( Adinolfi et al, 2012 ).…”
Section: Purinoreceptorsmentioning
confidence: 99%
“…Previous research has revealed that P2X7 receptors are expressed in various human cancers [22]. Recent studies have found an exosome/microvesicle and miRNA-dependent mechanism of P2X7 receptor having prometastatic activity in metastatic cancer [23,24].…”
Section: P2xrs and Their Role In Prostate Cancermentioning
confidence: 99%
“…Meanwhile, P2 receptor stimulation or agonist frequently results in an inflammatory response, which contributes to immune stimulation while also activating various immunosuppressive mechanisms, particularly in the tumor microenvironment [12][13][14][15]. P2 receptors are found in cervical, gastrointestinal, liver carcinoma, and prostate cancer cells and can activate esophageal cancer cell proliferation via the extracellular signal-regulated kinase 1/2 (ERK1/2) pathway [16][17][18][19][20][21][22]. The role of P2 receptors in prostate cancer has been underappreciated; thus, this review aims to summarize current knowledge in this area.…”
Section: Introductionmentioning
confidence: 99%